Karnataka Annual Plan 1981-82 Volume-V - Planning Commission (Planning Commission, 1981)
The Population of Sch. Tribes according to 1971 census in the state is 2,31 ,268 which works out to about 0.8 percent of the total population of the state. The percentage of literacy among Sch. Tribes according to 1971 census in 14.69 as against the general literacy percentage of 31.54 of the state. The Sch. Tribes are concentrated mainly in the districts of Mysore, Kodagu, Dakshina Kannada and Chickmagalur. Where the Tribal sub-plan schemes are in operation. The Sch. Tribes population covered under these schemes is 1,30,072 according to Bench Mark Survey conducted recently in the Tribal area. Thus about 53% of Sch. Tribes of the total population of Sch. Tribes in the state are covered under Tribal Sub-Plan.
Tribal Sub-Plan Planning Department